Optimal dose of bone marrow mesenchymal stem cell transplantation for experimental ulcerative colitis - Xiaoyun Chen; Yan Xia; Min Min; Lingzhi Qin; Yangsheng Liu (Regenerative Therapy)
Objective: To investigate the optimal dose of bone marrow mesenchymal stem cell-transplantation for the ulcerative colitis rat. Methods: The BMSC of SD rat were isolated, cultured and labelled with DAPI. SD rats were randomly distributed into 3 groups, Colitis was induced with immune-combined TNBS/ethanol in group A、B、C, 3 groups received caudal vein injection of 1 mL fluids, which contain cell number 1 × 106、5 × 106、1 × 107 separately. 5 rats in each group were sacrificed at day 7 and 14 after injection, Cryostat sections of gut, The number of BMSCs in colon and normal tissue surrounded was observed with fluorescent microscope. Results: The DAPI marked BMSCs could been seen in the colic mucosa in each group on day 7、14, more cells in colon than the surrounding normal tissue, compared with 1 × 106 group, More cells in 5 × 106 group (P < 0.05), there were no significant difference (P > 0.05) between 5 × 106 group and 1 × 107 group. There were more cells in colon on 14 day than 7 day, and less in the surrounding normal tissue on 14 day than 7 day. Conclusions: The density 5 × 106 is proper of bone mesenchymal stem cells for treatment of ulcerative colitis.